The Relationship Between Work Stress and Burnout in Nurses in the Inpatient Room of Mawaddah Medika Hospital - Suci Amalia Lajuba; Windu Santoso; Duwi Basuki (Journal of Nursing Management Innovations, 2025)
Background : Work stress can arise due to increasing job demands, role conflicts, unclear tasks, and the burden of responsibility that must be borne by the workforce. If left unattended for a long time, this condition has the potential to cause burnout.Aim : This study aims to determine the relationship between work stress and burnout among nurses in the inpatient room of Mawaddah Medika Hospital.Method : This study used a quantitative approach with a descriptive correlational design and a cross-sectional method. The sample consisted of 45 nurses selected through proportional random sampling. The instruments used were the Expanded Nursing Stress Scale (ENSS) questionnaire and the Maslach Burnout Inventory–Human Services Survey (MBI-HSS).Result : The results showed that most nurses experienced moderate work stress (73.3%) and moderate burnout (68.9%). The Spearman’s rank correlation test revealed a correlation coefficient of 0.865 with p = 0.000, indicating a significant relationship between work stress and burnout. Higher levels of work stress were associated with higher levels of burnout.Conclusion : There is a significant and strong relationship between work stress and burnout among nurses. Therefore, effective coping strategies are needed to help nurses manage work stress and prevent burnout.